2015
DOI: 10.1039/c5sm00665a
|View full text |Cite
|
Sign up to set email alerts
|

Design of a micellized α-cyclodextrin based supramolecular hydrogel system

Abstract: In recent years supramolecular structures built from macrocyclic compounds have attracted tremendous interest due to the unique properties derived from dynamic self-assembly. Our study proposes a two-step mechanism to form a supramolecular hydrogel system: (1) the formation of micelles, and (2) micelle association with α-cyclodextrin (α-CD) due to threading of PEGMA in the α-CD cavity, forming inclusion complexes. Using this mechanism, a supramolecular hydrogel made from a tri-component copolymer PLLA/DMAEMA/P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 65 publications
(29 citation statements)
references
References 66 publications
(107 reference statements)
1
28
0
Order By: Relevance
“…Our group studied shear‐thinning and self‐healing properties of supramolecular hydrogels with different types of polymeric entities ,. Dynamic rheological studies confirmed that non‐covalent inclusion complexation renders the sol‐gel process reversible subjected to shear and heating/cooling cycles.…”
Section: Types Of Noncovalent Polymeric Hydrogelsmentioning
confidence: 93%
See 1 more Smart Citation
“…Our group studied shear‐thinning and self‐healing properties of supramolecular hydrogels with different types of polymeric entities ,. Dynamic rheological studies confirmed that non‐covalent inclusion complexation renders the sol‐gel process reversible subjected to shear and heating/cooling cycles.…”
Section: Types Of Noncovalent Polymeric Hydrogelsmentioning
confidence: 93%
“…This section of the review discussed recent advances in supramolecular hydrogel assembly mediated by non‐covalent macrocylic host‐guest interactions. The concept behind host‐guest non‐covalent interactions (electrostatic, Van der Waals forces, π effects, hydrophobic effects) to form supramolecular hydrogels relied on the reversible binding between complementary host‐guest components ,. This section focused on recent development of supramolecular hydrogels through macrocyclic host components’ (e. g., cyclodextrins (CDs), cucurbit[ n ]urils (CBs), calix[ n ]arenes (CNs), and pillar[ n ]arenes) hydrophobic internal cavity to accommodate different guest molecules.…”
Section: Types Of Noncovalent Polymeric Hydrogelsmentioning
confidence: 99%
“…After cutting, the addition of competitive guests to the surface effectively prevented re-formation of the gel structure.Abdul Karim and Loh formed micellar hydrogels by hydrogen-bonding-driven crystallization of a-CD/PEG complexes. [80] Fort his,m icelles with ah ydrophobic PLA core and aP DMAEMA or poly-(oligo(ethylene glycol) methacrylate) (POEGMA) shell were formed in aqueous solution and subsequently cross-linked by crystallization with a-CD.Atopological hydrogel was recently presented by Takeoka and co-workers. [81] Extremely stretchable hydrogels were obtained by cross-linking a-CD-PEG rotaxanes with adamantyl stoppers.F or the covalent cross-linking,t he threaded a-CD units were converted into monomers and copolymerized with ionic monomers as well as NIPAM to obtain thermosensitive hydrogels.T he sliding cross-links resulted in highly stretchable gels.…”
Section: Hydrogelsmentioning
confidence: 99%
“…Quaternary ammonium PEI‐based materials have been used for a variety of applications such as to endow antibacterial activity to restorative composite resins, targeting against clinical isolates of pathogenic bacteria and for eradication of bacteria in water . Other polymers such as poly(2‐dimethylaminoethyl methacrylate) (PDMAEMA), which has been frequently used as a gene transfection agent, have cationic groups which can be used for antibacterial applications . Our group has previously shown that quaternization of amine‐containing polymers such as PDMAEMA result in a reduction of toxicity and enhance the effectiveness of the polymers against bacteria .…”
Section: Introductionmentioning
confidence: 99%